Efek Penyalahgunaan Neuroenhancement - Yulia Yulia Puspitasari (Yayasan Pendidikan Medika Indonesia, 2020)
Neuroenhancement is a controversial field of science and technology that has the potential to influence fundamental aspects of our mental functioning and behavior. This involves the use of neural technology to enhance cognitive, affective or behavioral function, which are not assessed as clinically impaired. There are various technologies that can produce neuroenhancing effects, such as drugs, gene editing, and brain stimulation. The use of recreational drugs by healthy individuals to improve cognitive or affective function is called pharmacological neuroenhancement (when it is explicitly used for performance-enhancing purposes in the workplace or in education. Drugs indicated for the treatment of psychiatric disorders such as attention-deficit hyperactivity disorder (ADD / ADHD) or Narcolepsy is the focus of the PNE debate because it also has cognitive enhancing effects in healthy individuals.Published research shows that drugs and non-invasive brain stimulation can enhance certain cognitive abilities in normal, healthy individuals, despite the strength of these effects and their generalizability. to non-laboratory conditions unknown.Also poorly understood at present are the possible negative consequences of the use of drugs that include a paradoxical decline in performance in some to the potential for dependence and addiction.